Purification and Charaterization of Protease from Pathogenic Bacteria Pseudomonas aeruginosa - Ace Baekhari; Maggy T Suhartono; Nurheni Sri Palupi; Tati Nurhayati (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2008)
In the last decade, concern on protease as medical target for overcoming bacterial diseases and viral diseases has been rapidly increased because of the obvious involvement of this enzyme in the molecular of the diseases. The purpose of this research was to purify and characterize protease from pathogenic bacteria Pseudomonas aeruginosa. The bacteria were grown in media containing triptone 1%, NaCl 1% and Yeast extract 0.5%. protease of Pseudomonas aeruginosa was purified using column chromatography with Sephadex G-100 gel. There were three peaks of enzyme protein, which were detected on fractions 14,17 and 30. the optimum pH of the extracelluler protease from Pseudomonas aeruginosa was 8. The optimum temperature of Pseudomonas aeruginosa was 300C. Fe3+ (1dan 5 mM) was strong activator and Co 2+ was strong inhibitor. Study on the effect of metals ion and specific inhibitors indicated that protease from Pseudomonas aeruginosa was serin metaloprotease. The apparent moleculer weights, as determined by SDS-PAGE and zymogram technique, 36 kD and 42 kD. Key word : Protease, characterization, purification, pathogenic bacteria P. aeruginosa